(untitled) (Bangladesh Medical Journal, 2016)
Non-cirrhotic portal hypertension (NCPH) is a heterogeneous group of liver disorders of vascular origin, leading to portal hypertension (PHTN) in the absence of cirrhosis.The lesions are generallyvascular, either in the portal vein, its branches or in the peri-sinusoidal area. The majority of diseases included in the category of NCPH are well-characterized disease entities where PHTN is a late manifestation. Two diseases that present only with features of PHTN and are common in developing countries are non-cirrhotic portal fibrosis (NCPF) and extrahepatic portal vein obstruction (EHPVO). Non-cirrhotic portal fibrosis is a syndrome of obscure etiology, characterized by obliterative-portovenopathy leading to PHT, massive splenomegaly and well-tolerated episodes of variceal bleeding in young adults from low socioeconomic backgrounds, having near normal hepatic functions. In some parts of the world, NCPFis called idiopathic portal hypertension in Japan or hepatoportalsclerosisin USA. Because 8595% of patient with NCPF and EHPVO present with variceal bleeding, treatment involves management with endoscopic sclerotherapy (EST) or variceal ligation (EVL). These therapies are effective in approximately 9095% of patients. Gastric varices are another common cause of upper gastrointestinal bleeding in these patients and these can be managed with cyanoacrylate glue injection or surgery. The prognosis of patients with NCPF is good and 5 years survival in patients in whom variceal bleeding can be controlled has been reported to be approximately 95100%. Bangladesh Med J. 2014 Sep; 43 (3): 170-176